Efektivitas dan Efisiensi Anggaran Pendapatan dan Belanja Desa (Apbdes) Dalam Pembangunan dan Pemberdayaan Masyarakat Tahun Anggaran 2015-2019 - Magdalena Silawati Samosir (Peneliti.net, 2021)
The background of this research is the low realization of the absorption of the Village Revenue and Expenditure Budget (APBDes) in Langir Village, and accompanied by the instability of the percentage of absorption of the Village Budget (APBDes) from Fiscal Year 2015 to 2019. This study aims to analyze the level of effectiveness and efficiency of the Village Revenue and Expenditure Budget in Community Development and Empowerment for the 2015 – 2019 fiscal year in Langir Village, Kangae District, Sikka Regency. The analytical tool used in this research is quantitative descriptive method, namely analyzing target data, expenditure realization and income by using the ratio of effectiveness and efficiency. While the data used are primary data and secondary data. The results of this study indicate that the average value of the effectiveness of the management of the 2015 - 2019 Village Revenue and Expenditure Budget in Langir Village, Kangae District, Sikka Regency is 85%, with the category of Quite Effective. Meanwhile, the average efficiency level is 40% in the Very Efficient category.